2019
DOI: 10.3390/rel10020128
|View full text |Cite
|
Sign up to set email alerts
|

We Have Come Back Home: The Spanish-Moroccan Community, Collective Memory, and Sacred Spaces in Contemporary Spain

Abstract: This paper examines the role of Islamic sacred spaces in Spanish-Moroccan identity negotiations in contemporary Madrid, Spain. In doing so, I explore how these sacred sites produce diverse meanings and practices that resist the Spanish states hegemonic narratives of place. I argue that the multilayered resistance via the “memory” and “place” of these sacred sites ostensibly reconciles and situates Spanish-Moroccans within the larger Spanish imagined community. The paper will first discuss the trans-local exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Alcántara-Plá and Ruiz-Sánchez (2017: 17) found that Islamophobic ideologies are so embedded in the Spanish media that when Muslims are mentioned on Spanish social networking sites, they are framed as military invaders and historical enemies. Other recent studies have examined the intersectional perspectives between Islamophobia and ethnicity (Bravo López, 2012), gender (Ramírez and Mijares, 2018), patriarchy (Guia, 2018), collective memory (Ouassini, 2019), immigration (Cea d'Ancona, 2016, policing and social control (Álvaro et al, 2015), recognition struggles (Dietz, 2004), and the impact of secular political identities on the presence of Islam in Spain (López Bargados, 2018).…”
Section: Spain Islamophobia and The Spanish Moroccan Communitymentioning
confidence: 99%
“…Alcántara-Plá and Ruiz-Sánchez (2017: 17) found that Islamophobic ideologies are so embedded in the Spanish media that when Muslims are mentioned on Spanish social networking sites, they are framed as military invaders and historical enemies. Other recent studies have examined the intersectional perspectives between Islamophobia and ethnicity (Bravo López, 2012), gender (Ramírez and Mijares, 2018), patriarchy (Guia, 2018), collective memory (Ouassini, 2019), immigration (Cea d'Ancona, 2016, policing and social control (Álvaro et al, 2015), recognition struggles (Dietz, 2004), and the impact of secular political identities on the presence of Islam in Spain (López Bargados, 2018).…”
Section: Spain Islamophobia and The Spanish Moroccan Communitymentioning
confidence: 99%